Sekuritisasi Transaksional dalam Krisis Venezuela: Analisis Politik dan Hukum Keamanan atas Penangkapan Nicolás Maduro - Sidratahta Muktar; Laurencius Simanjuntak; Aly Ashghor (Jurnal Keamanan Nasional, 2026)
This article examines the arrest of Venezuelan President Nicolás Maduro by the United States in January 2026 through the perspectives of security law and securitization theory. Although the operation was officially justified on the basis of narco-terrorism charges, the use of military force within the territory of a sovereign state raises significant questions concerning the principles of state sovereignty and international law. Employing a normative legal approach combined with the Copenhagen School's securitization theory, this study analyzes how Venezuela's strategic oil resources were discursively reconstructed as an existential threat to U.S. national security through the interaction of speech acts, audience acceptance, and political legitimization, thereby enabling the adoption of extraordinary measures. The findings indicate that the United States acted as the principal securitizing actor, portraying the Maduro regime as a national security threat while simultaneously advancing strategic interests related to energy security and access to Venezuela's oil resources. Building upon these findings, this article introduces the concept of transactional securitization, which explains how security discourse may function not only to legitimize exceptional security measures but also to facilitate strategic economic objectives. This conceptual development extends the explanatory scope of classical securitization theory by demonstrating that successful securitization may be followed by the political and economic reconfiguration of strategically valuable natural resources. From the perspective of international law, the Maduro case raises important questions concerning the principles of Permanent Sovereignty over Natural Resources (PSNR) and good faith in the exercise of state authority, while illustrating the increasingly blurred boundary between national security and geopolitical economic competition.